(untitled) (Baghdad Science Journal, 2022)
Breast cancer is the most prevalent malignancy among women worldwide, in Iraq it ranks the first among the population and the leading cause of cancer related female mortality. This study is designed to investigate the correlations between serum and tissue markers in order to clarify their role in progression or regression breast cancer. Tumor Markers are groups of substances, mainly proteins, produced from cancer cell or from other cells in the body in response to tumor. The study was carried out from April 2018 to April 2019 with total number of 60 breast cancer women. The blood samples were collected from breast cancer women in postoperative and pretherapeutic who attended teaching oncology hospital of the medical city in Baghdad and the serum markers evaluated by ELISA technique are Carbohydrate Antigen 15-3 (Ca 15-3), Carbohydrate Antigen 27.29 (Ca 27.29), Anti-Mullerian Hormone (AMH), Tumor Necrosis Factor-Alpha (TNF-α), Interleukin-6 (IL-6), Interleukin-10 (IL-10) and Human Epidiymis Protein-4 (HE4). Tissue samples were collected for the same breast cancer women who attended medical city, Baghdad with total number 30. The tissue markers evaluated by Immunohistochemical technique are Estrogen Receptor (ER), Progesterone Receptor (PR), Human Epidermal Growth Factor Receptor 2 (Her 2/neu) and Cyclin E. The results showed a positive significant correlation (p = 0.017) between Ca 27.29 and Her-2/neu, (p = 0.038) between IL-6 and cyclin E phenotype, (p = 0.051) between TNF-α and Cyclin E intensity, (p = 0.005) between HE4 and Her-2/neu, and negative significant correlation (p = 0.058) between IL-10 and ER score and (p = 0.045) between HE4 with Cyclin E intensity. We conclude from these correlations that positive correlations increasing disease progression, like correlation between Ca 27.29 and Her-2/neu, cyclin E with IL-6 and cyclin E with TNF-α. And the negative correlations may contribute to delay disease, like correlation between IL-10 and ER. From the correlations results in this study, it is clear that the Ca 27.29, Her-2 / neu, cyclin E markers play an important role in disease progression.